Implications of Mean-Reverting Measurement Error for Longitudinal Studies of Wages and Employment - Kim, Bonggeun; Solon, Gary (The Review of Economics and Statistics, 2005)
This note examines the implications of mean-reverting mea-surement error for two influential literatures based on longitudinal survey data: (1) the literature on real wage variation over the business cycle and (2) the literature on intertemporal substitution in labor supply. Accounting for mean-reverting measurement error suggests that real wages may be even more procyclical than indicated by recent longitudinal studies. We also find that the instrumental variables estimator commonly used in intertemporal substitution studies is inconsistent if changes in earnings and hours of work are measured with different degrees of mean reversion, but the magnitude of the resulting inconsistency appears to be small.